Parkinson's Disease Associated ?-Synuclein Familial Mutants Promote Dopaminergic Neuronal Death in Drosophila melanogaster. - Mohite, G.M.; Dwivedi, S.; Das, S.; Kumar, R.; Paluri, S.; Mehra, S.; Ruhela, N.; S, A.; Jha, N.N.; Maji, S.K. (ACS chemical neuroscience, 2018)
?-Synuclein (?-Syn) aggregation and amyloid formation are associated with loss of dopaminergic neurons in Parkinson's disease (PD). In addition, familial mutations in ?-Syn are shown to be one of the definite causes of PD. Here we have extensively studied familial PD associated ?-Syn G51D, H50Q, and E46K mutations using Drosophila model system. Our data showed that flies expressing ?-Syn familial mutants have a shorter lifespan and exhibit more climbing defects compared to wild-type (WT) flies in an age-dependent manner. The immunofluorescence studies of the brain from the old flies showed more dopaminergic neuronal cell death in all mutants compared to WT. This adverse effect of ?-Syn familial mutations is highly correlated with the sustained population of oligomer production and retention in mutant flies. Furthermore, this was supported by our in vitro studies, where significantly higher amount of oligomer was observed in mutants compared to WT. The data suggest that the sustained population of oligomer formation and retention could be a major cause of cell death in ?-Syn familial mutants.